INFORMATION DESCRIPTION AND DISCOVERY METHOD USING CLASSIFICATION STRUCTURES IN WEB - Uddin, Mohammad Nasir; Mezbah-ul-Islam, Muhammad; Gausul Haque, Kazi Mostak (Malaysian Journal of Library and Information Science, 2006)
Classification structures are useful for organising and finding information. The right use of classification structure in the web information architecture provides a user friendly interface and can serve as an effective tool for information retrieval. This paper defines the concepts related to the recent development in classification and gives an overview with case studies of using classification structure in information description and discovery in Web. The study found that hierarchical-enumerative structure is used mostly in directories, subject gateways and in cataloguing electronic contents. Faceted structure is used in the commercial sites to effectively organise and retrieve the web document through a multidimensional taxonomy. A third approach known as Folksonomy has emerged as a user oriented classification on the Web without maintaining any explicit relationship of classifying document. This study suggests using these three approaches in the appropriate context to ensure the optimum use of corporate information.